Relaciones entre el Tribunal Supremo y el Tribunal Constitucional en España - Tenorio Sánchez, Pedro J. (Revista de Derecho Político, 2016)
Abstract In Spain, Title VI of the Constitution considers the Supreme Court the highest judicial body in all orders, except for the provisions concerning constitutional guarantees, while art. 1 of the Organic Law of the Constitutional Court considers the Constitutional Court as the supreme interpreter of the Constitution. ach court should act as “supreme court” in its respective field, the Constitutional Court in the field of interpretation of the Constitution and the Supreme Court as far as the interpretation of ordinary legality is concerned. This is a widely accepted approach, both by the doctrine and even by the Constitutional Court. But as it is well known, sometimes the boundaries between the Constitution and ordinary law are not easy to establish, and, in those cases, self-restraint by the supreme interpreter of the Constitution is in order. In fact, that our Constitutional Court does not annul many Supreme Court decisions may be true to say. Analyzing the number of resolutions of the Supreme Court, reviewed by the Constitutional Court between 2001 and 2011, in relation to the number of Supreme Court decisions that were overturned, we found a range between 0,31% and 1% -just one year- with an average of less than 0,5%. The year when most resolutions were canceled, 2001, 1710 resolutions were reviewed and 19 judgments were overturned.